Performance pay across Europe: Drivers of the increase and the link with wage inequality - Wouter Zwysen (European Trade Union Institute (ETUI), 2021)
This paper shows that the use of performance pay schemes has risen substantially across Europe from fewer than one-fifth in 2000 up to one-third in 2015, using data from the European Working Conditions Survey and the Structure of Earnings Survey enriched with external contextual data. This increase has been partly driven by technological change and increased openness to trade, particularly through a rising use of bonuses or shares linked directly to firm performance. Institutional factors such as employment protection legislation and collective pay agreement coverage also play an important role. Performance pay may contribute to wage inequality through two channels: (a) workers receiving it generally already have higher earnings and work in high-skilled jobs; and (b) compared to other similar workers in similar positions, those receiving performance pay earn 7 to 9 per cent more. The increase in inequality is not a given, however, as strong employee representation is associated with a more equal distribution of these wage gains.
Keywords: 330; performance fee; wage structure; EU countries; Leistungsentgelt; Lohnstruktur; EU-Staaten